The real Soviet Russia. Transl. from the Russian by J. Shaplen (Yale University Press, 1945)
With index. Publ. on the Foundation established in memory of Amasa Stone Mather of the class of 1907 Yale college. David J. Dalin is pseud. of David Jul'evič Levin.